Chloride corrosion resistance of cement mortar with recycled concrete powder modified by nano-silica. (18th January 2023) - Liu, Xiaoyan; Liu, Ruidan; Xie, Xian; Zuo, Junqing; Lyu, Kai; Shah, Surendra P.
Highlights: The chloride content in RCP mortar is evaluated at different immersion time. The relationship between macro performance and microstructural characteristics of NS enhanced RCP mortar is established. The effect of NS on the chloride corrosion resistance of RCP mortar is investigated. An optimal NS dosage of 2% reflected by the greatest chloride corrosion resistance is obtained. Abstract: In the marine environment, the service life of coastal structures can be significantly reduced on account of chloride corrosion. This study employed nano-silica (NS) to improve the chloride corrosion resistance of mortar samples prepared with recycled concrete powder (RCP). The free chloride ion concentration and mechanical strength of mortar samples in 3.5% NaCl solution up to 12 months were measured. Rapid chloride migration (RCM) and electric flux experiments were carried out. Compared with the pure RCP mortar, the 2% NS incorporated RCP mortar experienced a significant decrease in the chloride ion diffusion coefficient, electric flux and corrosion rate of internal rebar. Moreover, the RCP mortar with 2% NS also had the slowest increase in the free chloride ion concentration and surface chloride ion concentration. The addition of RCP in cement mortar reduced the chloride corrosion resistance, while the inclusion of 2% NS compensated for the RCP induced degradation, resulting in an improvement in chloride corrosion resistance. The X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) results showed that the addition of RCP and NS consumed Ca(OH)2 to generate more C-S-H gels and C-A-S-H gels and thereby improved the physical chloride-binding ability of the sample. In addition, the formation of Friedel's salt via the combination of chloride ion with aluminosilicate further improved the chlorine ion corrosion resistance.